The Impact of Social Media for Hand Surgeons: A Prevalence and Correlation Study With Online and Academic Reputations - Sameer R. Khawaja, BS; Krishna N. Chopra, MA; Musab Gulzar, BS; Ozair R. Khawaja, HS; Shammah E. Udoudo, BS; Joseph G. Monir, MD; Michael B. Gottschalk, MD; Adrian L. Huang, MD; Nina Suh, MD; Eric R. Wagner, MD, MS (Journal of Hand Surgery Global Online)
Purpose: This study examines the influence of social media use among orthopedic and plastic-trained hand surgeons on patient-reported ratings online and academic productivity. Methods: The American Society of Surgery of the Hand directory was queried for actively practicing orthopedic and plastic surgeons with a hand surgery fellowship. Each name was searched on various social media platforms. Average ratings, number of reviews, and number of comments were collected from Healthgrades, Google reviews, and Vitals. H-index was searched on Scopus. A summated social media presence score was calculated to identify the top 20% of social media users in each cohort. Results: A total of 97 orthopedic and 102 plastic surgeons were included. Overall, plastic surgeons were more active on social media compared to orthopedic surgeons. There was a positive association between having active profiles and Healthgrades ratings. When looking within the subgroups, the top 20% of social media orthopedic users were found to have a significantly higher mean Healthgrades rating and a mean number of comments than the rest of the cohort. On Vitals, the top 20% of social media users had higher mean ratings compared to the remaining 80%. The top 20% of plastics social media users had a significantly higher average Healthgrades rating compared to the rest of the plastics group. On Google reviews, the top 20% also had higher mean ratings, as well as mean number of ratings, compared to the rest of the cohort. Plastic surgeons with a Twitter/X account had a significantly higher h-index than plastic surgeons without a Twitter/X account (14.5 vs 9.2, P < .05). Conclusions: Social media involvement is positively associated with surgeon ratings and the number of reviews and comments on physician rating websites. Using web-based marketing tools is still rare in hand surgery, especially among orthopedic surgeons. Type of study/level of evidence: Economic/decision analysis IV.